Microsurgery - Huaraca , Walter Francisco (Revista Universidad de Guayaquil, 2010)
Microsurgery is a very important part of plastic surgery allows the surgeon experienced in mi- crosurgery to repair any defects in the body, be it congenital, acquired or traumatic. It can be applied safely in adults and children.2 The success of these microsurgical procedures lie in the preoperative planning, which is a significant task and will have a direct bearing on the outcome of the procedure, the patient selection, surgical planning, selection donor site, the viability of transferred tissues and technical aspects of microvascular anastomosis are very important, however an error in one of these aspects lead to the failure of free flaps. There are some factors such as age, patients undergoing radiotherapy and several systemic diseases such as atheroscle- rosis, diabetes, cardiovascular limiting its application.
Keywords: Microsurgery; Free flap; Autólogous tissue reimplantation; Plastic surgery; Reconstructive surgical procedures.